Cumplimiento de las metas del año 2018 en la concesión de créditos de la Cooperativa San Antonio del cantón Montalvo - Intriago Vega, Anita De Jesús (2020)
From its origins at the beginning of the twentieth century, Cooperativism in Ecuador, did not have a support, or significant interest on the part of the state, this impetus for these entities to look for a fruitful development, promoting creativity in search of new financing alternatives o capitalization for its activities; from the perspective of the union of partners in search of achieving the socioeconomic development of productive sectors such as retail merchants, transporters, farmers, craftsmen among other groups, establishing savings and credit cooperatives. The savings and credit cooperative San Antonio Ltda .; It is an entity that seeks to be a reference of the momentum, growth and sustainable development for its members, by injecting a financing of effective capital, which allows them to encourage their activities or production, achieving a mutual benefit between the entity and its partners or beneficiaries. This is one of the purposes of the financial entity that seeks to have economic performance, growth and development, which will allow it to meet the challenge of becoming a consolidated entity. The growth of a loan portfolio is a fundamental component to reach the expected expectations, which must be maintained in a favorable percentage of increase between each accounting period. The collection area seeks to find the most strategic way possible to achieve compliance with its budgeted projections. Under this approach, the analysis of the Compliance of the Goals in the Credit Concession of the Cooperativa San Antonio Ltda., Of the Canton Montalvo, plays an important role for the entity in determining the impact of the economic behavior and the effectiveness in the credit process.